(untitled) (Kairaranga, 2004)
Bullying occurs in most schools and happens to students no matter how capable, popular and well-adjusted they are. This paper reports on a study that examines the nature and extent of bullying and explores the context of bullying and school violence in New Zealand schools. Approximately 1370 students from seven primary and three secondary schools participated in the study. Using a survey approach, a questionnaire was designed to examine the prevalence and incidence of different types of bullying; the nature of the actual bullying and where it is most likely to happen: schools responses to bullying, including the issues of reporting and why students choose not to tell. Results indicate that all of the participating schools reported bullying to a greater or lesser extent. Listening to the voices of students in this study extends understanding of the issues around bullying. The results led to recommendations based on issues of policy, supervision (particularly in the areas Identified by the students as being hot spots) and the need to communicate with an emphasis on reporting and the need to create a culture of "safe telling" to ensure safe emotional learning environments for all students.